Good Governance and Public Trust - Fandi Prasetya (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
The success of a democratic country is the increasing public trust in the government. With increasing public trust, it is hoped that the community can participate in the government development process. One way that can be done to increase trust is good governance. Good governance itself consists of responsiveness, accountability, and transparency. However, in Indonesia, people's trust in the government has declined, contributing to the ineffectiveness of the government's performance. The number of corruption cases in Indonesia has also caused a decline in public trust. Therefore, this study aims to determine whether responsiveness, accountability, and transparency affect public trust. The novelty of this research is the use of data processing methods. The research method used was distributing questionnaires and then processing the data using SEM PLS. The research results show that responsiveness, accountability, and transparency affect public trust. The results of this study are anticipated to help government institutions promote good governance and boost community trust. Furthermore, this research is expected to enhance the community's understanding of the importance of information and communication technology in evaluating government performance.